O valor de existência de um ecossistema costeiro tropical, através da disposição ao trabalho voluntário - Fonseca, Sérgio de Mattos (2001)
The efforts for placing economic value on natural resources pose difficult questions in terms of current socio-economicand ecological paradigms. Use values, identifiable by formal economic methods, must be complemented by investigations about the actual importance that common citizens attribute to ecosystems. This leads to the value of existence, quite difficult to extract, as it involves subjective components of culture and ecology. Applying the Contingent Valuation Method (CVM), complemented by the component of voluntary work, it is possible to reduce the bias of underdevelopment, and other bias, that make it difficult to identify the willingness to contribute to the reclamation and/or preservation of ecosystems. This research effort estimated the value of existence, applying the CVM, comparing the Willingness to Pay with the Willingness to Work voluntarily in favor of the recovery and preservation of a tropical coastal ecosystem. The figues reached for the value of existence of the Itaipu lagoon, in Niteroi, state of Rio de Janeiro, Brazil, were US$2,225,328.00, using Wllingness to Pay, and US$7,992,000.00, using Willingness to Work voluntarily.